Dataset on the quality of life and neurocognitive effects of prophylactic cranial irradiation, with and without hippocampal avoidance, in small-cell lung cancer patientsMendeley Data - Luis Heredia; Mauricio Murcia-Mejía; Margarita Torrente (Data in Brief)
This article presents data collected from 15 patients diagnosed with small-cell lung cancer who received prophylactic cranial irradiation (PCI), with or without hippocampal avoidance. Patient assessments included two specific questionnaires related to quality of life and an extensive neurocognitive evaluation. The evaluation covered various domains: verbal short-term memory, working memory, visuoconstructive abilities, visuospatial memory, semantic memory, verbal fluency, cognitive flexibility, inhibitory control, selective and divided attention, and processing speed. Assessments were conducted prior to PCI and at 3, 6, 12, and 24 months post-treatment.Despite the limited sample size due to challenges in patient recruitment and comprehensive follow-up, the data presented may help to identify the neuropsychological domains most affected in this population and can be useful in the design of future larger-scale studies. At present, there is limited information regarding the neuropsychological profiles of these patients and most studies focus on only one or two neuropsychological domains, typically emphasizing working memory assessments.